European currency system: problems and developments of prospective evaluation (Economics and region, 2019)
In the article the authors investigated the problems of the European monetary system functioning. It is emphasized that the EU and the Euro zone are currently suffering from strain and unsolved problems, which do not exclude gradual decrease in the EU countries consolidation and influence.The aim of the article is to analyze present days’ problems of European Union functioning and European monetary system, in particular evaluation their further development perspectives.Debt crisis in the Euro zone sets a question to the single European currency and European integration prospective. It is noted by the authors that as a result of economic crisis Europe are divided into two macro regions, which are unsuccessful “South” and prosperous “North”. Numerous prognoses foresee various scenarios for the situation development, from pessimistic to optimistic ones. However political efforts of the leading EU countries, primarily Germany, France, and the Netherlands are required.
Keywords: European currency system; the Euro zone; European Union; European integration; euro